MTHFR GENE POLYMORPHISM AMONG BHILS OF UDAIPUR, RAJASTHAN - Banerjee, Bhaswarupa; Saraswathy, Kallur Nava (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Methylenetetrahydrofolate reductase (MTHFR) ,an enzyme that in humans is encoded by theMTHFR gene, has a crucial role in regulating cellular methylation, through the conversion of 5,10-methyl-tetrahydrofolate(THF) to 5-methyl-THF, the methyle donor in the transformation ofhomocysteine to methionine. Reduced MTHFR activity due to the C677T change has beenassociated with different disorders, eg:, vascular disease, neural tube defects, Down’s syndrome andpreeclampsia and spontaneous abortions. Moreover, many studies have showed the association ofthis polymorphism with the risk of colon, ovarian and breast cancer. The aim of the study is to screenMTHFR C677T single nucleotide polymorphisms among Bhils of Udaipur, Rajasthan and tocompare our results with Indian and world populations. In present study a total number of 78samples (both blood and buccal) were taken from randomly selected individuals (both males andfemales, unrelated upto first cousins). DNA extraction from samples was done by using High YeildGenomic DNA extraction kit (Real Biotech Corporation) and Gentra Puregene Buccal Kit. Furtherusing other molecular techniques like PCR-RFLP using Hinf I and gel electrophoresis. In the presentstudy MTHFR gene is found to be polymorphic among the Bhils of Rajasthan with maximum numberof CC (92.31%) genotype followed by CT (6.41%) and least by TT (1.28%) genotype. The populationis not in the Hardy Weinberg Equilibrium with respect to the MTHFR polymorphism (P<0.05).